Determination of Xanthophyll and Carotene in Marigold Petal for Dye Purposes - Sompian Kasemsap; Permsak Suthevaree; Warunee Warunyanond; Amorn Pethsom (Agriculture and Natural Resources, 1990)
Analysis of pigments in petals of various marigold cultivars grown at Experimental Plot II, Department of Horticulture, Kasetsart University and at Royal Ang Khang Station revealed that xanthophyll and carotene contents in both fresh and dried petals as determined by AOAC and WRRL methods varied among cultivars and flower color groups. The cultivars with orange flowers especially Toreador was suitable for dye purposes. This cultivar yielded more xanthophyll and carotene contents when grown at Royal Ang Khang Station than at Bangkhen. Suitable cultivars that should be grown for dye at both Bangkhen and Royal Ang Khang Station in order of xanthophyll content are Toreador, Orange Lady, Pumpkin Crush, Apollo, Matador and Red Brocade with the respective xanthophyll contents of 15,249.54, 13,751.34, 13,376.79 13,323.28, 12,918.73 and 11,985.60 ppm.